SOSIALISASI CARA MELAKUKAN TINDAKAN AWAL GAWAT DARURAT PADA KECELAKUAAN LALU LINTAS DI IGD RSUD KARAWANG - Grace Evelyn; Rina Fera (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Traffic accidents are certainly avoided every time you use the road, sometimes traffic accidents occur suddenly due to poor road infrastructure or due to negligence of road users resulting in minor injuries to serious injuries and an emergency level. The urgency of a situation where there is a critical condition and causes death so that first aid is very important. Some of the family's knowledge of first aid is confusing to the family. This service is carried out to provide socialization to patients and families on how to take emergency action first aid with traffic accident first aid at the Karawang Hospital Emergency Room in 2021. This service was carried out in June 2021. Respondents in this study totaled 40 respondents whose families experienced traffic accident visit to Karawang Hospital Emergency Room. The results of family knowledge with good first aid amounted to 20 respondents (90.9%), with a p-value of 0.011. This shows a value of less than 0.05, meaning that there is a relationship between family knowledge and first aid for traffic accident patients in the Karawang Hospital Emergency Room in 2021. Improving emergency services and permanent procedures for service delivery, community outreach about first aid for traffic accidents, especially good orally and visually in the Karawang Hospital Emergency Room